Evaluation of the role of polyelectrolytes in membrane filtration - Wong, Evelyn Shu Li (2021)
The usage of polyelectrolytes in membrane modification has gained great popularity in recent years. Some aspects relating to the polyelectrolyte-modified membranes, however, have not been evaluated in the previous works. In this paper, the roles of various types of polyelectrolytes on membrane filtration in various applications are evaluated and the characterisation results of polyelectrolyte-modified membranes to membrane filtration performance in various applications are also studied. The deposition of polyelectrolytes onto the membrane has changed the membrane’s nature and properties. The modification changes have greatly benefited the micropollutants and foulants removal from water. Seven studies using different types of polyelectrolytes and membrane support are studied and evaluated. Furthermore, several characterisation methods such as FTIR, contact angle measurements, SEM, AFM, and XPS are characterised based on different methods. The usage of zwitterionic PMPC-co-AA has decreased the membrane fouling and has a very stable membrane performance. Next, the usage of spin-assisted LbL assembly is preferable due to its simplification operation and is timesaving. Moreover, the polyelectrolytes of CHI and ALG biopolymers are recommended as they are biocompatible, adaptable material, versatile, non-toxic, easy to obtain, and most importantly, biodegradable. Last but not least, the most used deposition method is the LbL assembly. However, an improved LbL assembly and more environmentally friendly materials usage have not been expansively investigated.